Narrative architecture and level design: analysis of The Witcher III: Wild Hunt (2015) (Research, Society and Development, 2023)
This work aims to investigate the relevance of architecture to level design in virtual games, taking as study object the game The Witcher III: Wild Hunt (2015). To construct a building, it is needed to make a data collection of one's necessities, planning and organizing resources to accomplish the user’s expectations. In the development of video games scenarios, it is essential to replicate these efforts by adapting them to the virtual worlds to facilitate the connection between the player and the game. To analyze how these techniques are applied in the virtual environment and what is its result, the bibliographical research method was used based on authors from both fields, architecture and game design. The study unfolded through the explanation of one field's ideas and their encounter to similar thoughts on the other area. Throughout this exam, it was concluded that the adoption of such ideas in The Witcher III: Wild Hunt (2015) simplifies the goals comprehension process, mobility and user’s immersion.